Is mathematics still scary? Primary school pupils' perceptions of mathematics - Mubarik; Ibnu Hadjar; Welli Meinarni; Annisa Dwi Kurniawati (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
For a long time, research has shown that mathematics is an unpleasant subject. This study examines whether mathematics remains scary today. Previous research has limitations, particularly in terms of why primary school students have negative perception of mathematics. This study uses a descriptive qualitative design supported by quantitative data to obtain more in-depth results. The subjects of this study were 153 fifth-grade students from nine primary schools in the city of Palu, selected at random. Data were collected via a questionnaire, and responses were categorized as positive or negative. Based on this, 109 students (71%) gave negative responses, namely